Learning shooting sports : archery, rifle, pistol - Barth, Katrin , 1966-; Dreilich, Beate (Meyer & Meyer Sport, 2010)
Suitable for children who are beginning to practice one of the many shooting sport disciplines, such as crossbow, archery, rifle, pistol, and target shooting, this title contains information about equipment, techniques and your physical fitness. It offers tips for practicing at home and we will tell you how to recognize and avoid mistakes